PENGEMBANGAN MEDIA PEMBELAJARAN MEKANIKA TEKNIK BERBASIS ANIMASI DI SMK TEKNIK GAMBAR BANGUNAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA (UJI COBA PENGEMBANGAN PRODUK DI SMK N 2 SUKOHARJO) - Probowati, Inayah; Rahmawati, Anis; Sukatiman, Sukatiman (Pendidikan Teknik Bangunan, 2015)
This study?s aims to determine: 1) The development of media-based learning procedures is well animated on the subject of Technical Mechanics. 2) The feasibility of theanimation-based instructional media on the subjects of Technical Mechanics. 3) The learningoutcomes of student learning after using animation-based instructional media on the subjects of Technical Mechanics. This research is a Research and Development (R & D). Sources of data are obtained from literature sources and the development of Technical Mechanics?s learning media based on animation using Microsoft PowerPoint 2010. Determination of eligibility level based by learning media animation based on validation testing by experts and validation by students through a questionnaire. Improving student learning outcomes after the using of instructional media developed is known by comparing the results of pre-test and post-test students. Based on the results of this study concluded: 1) Procedure animationbased learning instructional media development was: (a) Analysis ofneeds; (b) Preparation of animation media-based learning; (c) Testing; (d) Revision; (e) The final product. 2) Product learning media based animations that have been developed by researcher to be feasible for using in the learning process Mechanics of Technical at SMK based on testing ofthe experts and students. 3) Student learning outcomes after following lessons process using animation-based instructional media increased.Keywords: Technical Mechanics, media, animation, Microsoft PowerPoint, learning outcomes